A finite element study for tibial fractures: analyze the biomechanical condition of the tibial fracture area to provide guidance for subsequent treatment - Zhang, Ke-Rui; Luo, Bin; Tu, Ju; Li, Ya-Qin; Wen, Jun; Shen, Chang-Yong; Jia, Xue-Hai; Deng, Yi; Ma, Li-Tai; Yang, Yi (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionDistal tibial fractures are common fracture sites and usually require surgical treatment to achieve anatomical reduction. Intramedullary nails (IMN) are widely used in orthopedics for stabilizing fractured bones and treating limb deformities. The process of postoperative bone healing is of great significance for patient rehabilitation and can guide subsequent treatment methods. However, the current radiographic techniques used to determine the degree of fusion, such as X-ray, need to be improved in accuracy and have some radiation effects. Several studies suggested that the mechanical load on the fracture area could reflect the bone healing process and evaluated the stability of fracture area. The aim of this study is to investigate the biomechanical changes in the fracture area during bone healing and IMN, and to prepare for the subsequent placement of intelligent stress and displacement sensors based on the changes in stress and displacement, in order to provide guidance for the treatment and rehabilitation of postoperative fractures.MethodsFinite element (FE) models representing different healing stages of tibial fractures were developed. All conditions were applied to simulate the stress and strain of the IMN fixation system under normal tibial stress.ResultsThe stress at the fracture area on the IMN gradually decreases, while the stress on the callus gradually increases until reaching a stable state at the 12th week after surgery. And the deformation value and the displacement value of the callus decrease and stabilize over time. Based on the changes in stress at the fracture area of the IMN and the displacement value of the callus, we can place a stress sensor at the fracture area of the IMN and a displacement sensor at the callus area.ConclusionThis study utilized FE analysis to evaluate stress, deformation and displacement between the IMN and bone during the healing process of tibial fractures in four stages. By combining these aspects, the degree of bone healing can be assessed. This research enables orthopedic doctors to monitor the progression of fracture healing without relying solely on imaging examinations. Furthermore, it aids in guiding patients to undergo appropriate rehabilitation training for better recovery.